Ethnic Relations between Lithuanians and Poles in the Eastern and South-Eastern Part of Lithuania 1960–1985 - Stravinskienė , Vitalija (Genocidas ir rezistencija, 2016)
The article explores the manifestation of the Soviet national policy in the eastern and south-eastern part of Lithuania during the Khrushchev Thaw period and the Brezhnev Era of stagnation by focusing on the ethnic relations between Lithuanian and Poles who, in terms of numbers, dominated in the region. The situation in the eastern and south-eastern part of Lithuania (multi-ethnic population, geographical location, historical heritage, etc.) was very favourable for the implementation of the Soviet national policy. Based on the slogans of “friendship between nations” and “internationalism”, the concept of the convergence of the nations was realised. It manifested in closer relations between various ethnic groups, soviet republics and their population. As far as eastern and south-eastern part of Lithuania was concerned, relationships were promoted with neighbouring republics, firstly with Belarus, rather than with other regions of the Republic of Lithuania. Such policy led to the formation of a specific situation in Vilnius region. A certain part of the inhabitants of the region more often identified themselves with the Belarusian population and had a poor understanding of the life of other regions in Lithuania. This determined segregation between the Lithuanian and Polish communities, and alienation of the Poles. The Soviet authorities controlled ethnic relations between Lithuanians and Poles; any potential ethnic tension was immediately repressed and hardly ever surfaced. Ethnic disagreements between Lithuanians and Poles (due to different interpretation of historical past, etc.) were frozen for several decades and broke out only at time of the decline of the Soviet period. The position of the Polish population in the region was fuelled by attention and support from the Polish authorities and society. However, only relationships sanctioned by the Soviet authorities were allowed. Therefore any nationalist ideas from Poland were immediately stifled. Seeking faster indoctrination of the population, the Soviet authorities used the Polish language factor in the eastern and south-eastern part of Lithuania. The Polish population in this region was provided an opportunity to develop education and culture in their mother tongue, yet this was controlled and Sovietised. The support for nurturing the Polish ethnic identity by the Soviets formed a stereotype among Lithuanians that Poles were protected and the eastern and south-eastern part of Lithuania was deliberately Polonised. In the 1970s, when attempts to consolidate the society in the USSR were made on the basis of the Russian language and culture, assimilation efforts (Russification) strengthened in Lithuania. This process particularly affected the position of the Poles in the eastern and south-eastern part of Lithuania (Polish schools became Russian schools, the number of mixed marriages increased, the Russian language was increasingly used for communication, etc.). Such policies led to the assimilation of certain part of the Polish population in the region.